2012
DOI: 10.1016/j.otsr.2012.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Critical study of resection margins in adult soft-tissue sarcoma surgery

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 37 publications
5
36
0
2
Order By: Relevance
“…Extensive surgery is associated with increased patient morbidity, that is difficult to justify if the patient ultimately dies from metastatic disease or experiences rates of local tumour recurrence similar to that achieved by a more conservative resection. In human studies on soft tissue sarcoma management, the challenge of balancing local surgical aggression with the need for effective local tumour control, patient morbidity and the risk of tumour metastasis is the focus of considerable debate . Several authors have determined that while the development of metastatic disease is not influenced by the extensiveness of local surgery, incomplete tumour resection is consistently associated with poor overall survival .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive surgery is associated with increased patient morbidity, that is difficult to justify if the patient ultimately dies from metastatic disease or experiences rates of local tumour recurrence similar to that achieved by a more conservative resection. In human studies on soft tissue sarcoma management, the challenge of balancing local surgical aggression with the need for effective local tumour control, patient morbidity and the risk of tumour metastasis is the focus of considerable debate . Several authors have determined that while the development of metastatic disease is not influenced by the extensiveness of local surgery, incomplete tumour resection is consistently associated with poor overall survival .…”
Section: Discussionmentioning
confidence: 99%
“…How wide the excision margin needs to be for effective control of the soft tissue sarcoma is the topic of considerable debate in both human and veterinary literature . Several human studies have suggested that the incidence of recurrence for soft tissue sarcoma is similar in patients with margins of less than 1 mm and greater than 1 mm, and recurrence can still occur in patients reported with clean margins . The cause of recurrence in patients with histologically clean margins is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative tumour margins lower local recurrence rates and improve long-term survival 14 15. Indeed, the wider these resection margins the better, especially with poorly differentiated tumours, which may have satellite lesions and a greater predisposition to local recurrence 16. In the event of tumour invasion or compression of an important adjacent structure, the surgeon must consider the risks and benefits of either partial resection of the adjacent structure or careful dissection around the tumour with a higher likelihood of leaving a positive resection margin 13.…”
Section: Discussionmentioning
confidence: 99%
“…This may occur because of high-grade histology,16 because the tumour may not be encapsulated but possess finger-like projections into the surrounding tissue23 or because of a high likelihood of positive resection margins. If local recurrence is likely, a temporary method of abdominal wall reconstruction may be used.…”
Section: Discussionmentioning
confidence: 99%